PENGARUH MOTIVASI BELAJAR DAN KETERAMPILAN PROSES SAINS TERHADAP PEMAHAMAN KONSEP FISIKA SISWA - Febrianti M.; I Dewa Putu Nyeneng; Nengah Maharta (Jurnal Pembelajaran Fisika, 2013)
The purpose of this research to determine: (1) the linear positively and significantly influence of learning motivation toward understanding concept by using Learning Cycle 5E (LC 5E); (2) the linear positively and significantly influence of skill process science toward understanding concept by using LC 5E; (3) the linear positively and significantly influence of study motivation and skill process science toward understanding concept by using LC 5E. The population is all of students in class X SMAN 1 Natar. The sample are students of class X2 amount 36 students. The sample class is selected by cluster random sampling. Design of this research is one-shot case study. The results are: (1) there are a linear positively and significantly influence of learning motivation toward understanding concept by using LC 5E and it contributed 35,1%; (2) there are linear positively and significantly influence of skill process science toward understanding concept by using LC 5E and it contributed 53,5%; (3) there are linear positively and significantly influence of study motivation and skill process science toward understanding concept linear positively and significantly by using LC 5E and it contributed 58,8%. Keywords : Learning Motivation, Skill Process Science, Understanding Physics Concepts, and LC 5E